Case report: Difference in outcomes between two cases of Hailey-Hailey disease treated with apremilast - Yamaga, Misako; Miyauchi, Toshinari; Peh, Jin Teng; Itamoto, Sota; Mai, Yosuke; Iwata, Hiroaki; Nomura, Toshifumi; Ujiie, Hideyuki (Frontiers in Genetics, 2022)
Hailey-Hailey disease (HHD) is a rare autosomal dominant acantholytic dermatosis clinically characterized by recurrent erythematous plaques and erosions mainly on the intertriginous regions. Although HHD seriously affects quality of life, conventional treatments often fail to provide long-term relief for most patients. The effectiveness of the phosphodiesterase-4 inhibitor apremilast on severe HHD was first reported in 2018, and it is currently expected to be established as an efficacious and safe therapeutic option in the future, after further testing. Here we report two cases of HHD treated with apremilast which showed opposite outcomes. Although the case with extremely severe symptoms showed remarkable and long-lasting effectiveness with apremilast, the other, with milder symptoms, showed no improvement. The former highlights the potential of apremilast as a treatment option for HHD, especially in cases where conventional treatments have failed. The latter, however, underlines the difficulties in managing HHD and the complexity of its disease background.